2013
DOI: 10.1088/0004-637x/773/2/179
|View full text |Cite
|
Sign up to set email alerts
|

The Gemini Planet-Finding Campaign: The Frequency of Giant Planets Around Debris Disk Stars

Abstract: We have completed a high-contrast direct imaging survey for giant planets around 57 debris disk stars as part of the Gemini NICI Planet-Finding Campaign. We achieved median H-band contrasts of 12.4 mag at 0.5 ′′ and 14.1 mag at 1" separation. Follow-up observations of the 66 candidates with projected separation < 500 AU show that all of them are background objects. To establish statistical constraints on the underlying giant planet population based on our imaging data, we have developed a new Bayesian formalis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 82 publications
4
108
1
Order By: Relevance
“…There may be even more tension with the form of the mass distribution, which in RV surveys, is a power law increasing sharply toward low masses. Wahhaj et al (2013b) found a positive power law index for the distribution in planet mass (more massive objects are more common), in sharp disagreement from the RV findings. This result, however, was driven by their inclusion of the four HR 8799 planets as independent detections and their lack of any detected companions 5 M J .…”
Section: Limits On An Rv Distribution Functioncontrasting
confidence: 67%
“…There may be even more tension with the form of the mass distribution, which in RV surveys, is a power law increasing sharply toward low masses. Wahhaj et al (2013b) found a positive power law index for the distribution in planet mass (more massive objects are more common), in sharp disagreement from the RV findings. This result, however, was driven by their inclusion of the four HR 8799 planets as independent detections and their lack of any detected companions 5 M J .…”
Section: Limits On An Rv Distribution Functioncontrasting
confidence: 67%
“…For HIP 11360, the star is classified as a β Pic member in NICI papers, while we adopt membership in the Tucana association, based on our revised system RV. For HD 61005, we adopt membership in Argus (40 Myr) while Wahhaj et al (2013) adopt an age of 100 Myr without assigning membership to any known group. Finally, HIP 71908 is included in the Her-Lyr membership in Biller et al (2013), while we claim it is a significantly older star with similar kinematics.…”
Section: Stellar Agesmentioning
confidence: 99%
“…We performed MLOCI reductions on ten methane-band (CH 4 S, λ = 1.578 μm) datasets from the Gemini NICI PlanetFinding Campaign (2008Liu et al 2010;Wahhaj et al 2013b;Nielsen et al 2013;Biller et al 2013). The filter was designed to help detect methane, which is usually found in the atmospheres of cool substellar companions with surface temperatures <1400 K. In this work, the simultaneously exposed images in filter CH 4 L were not used for spectral differencing because we wanted to keep the analysis simple.…”
Section: Observations and Data Reductionmentioning
confidence: 99%